Actin sliding velocity on pure myosin isoforms from hindlimb unloaded mice. (30th June 2014) - Maffei, M.; Longa, E.; Qaisar, R.; Agoni, V.; Desaphy, J.‐F.; Camerino, D. Conte; Bottinelli, R.; Canepari, M.
Abstract Aim Notwithstanding the widely accepted idea that following disuse skeletal muscles become faster, an increase in shortening velocity was previously observed mostly in fibres containing type 1 myosin, whereas a decrease was generally found in fibres containing type 2B myosin. In this study, unloaded shortening velocity of pure type 1 and 2B fibres from hindlimb unloaded mice was determined and a decrease in type 2B fibres was found. Methods To clarify whether the decrease in shortening velocity could depend on alterations of myosin motor function, an in vitro motility assay approach was applied to study pure type 1 and pure type 2B myosin from hindlimb unloaded mice. The latter approach, assessing actin sliding velocity on isolated myosin in the absence of other myofibrillar proteins, enabled to directly investigate myosin motor function. Results Actin sliding velocity was significantly lower on type 2B myosin following unloading (2.70 ± 0.32 μm s−1) than in control conditions (4.11 ± 0.35 μm s−1), whereas actin sliding velocity of type 1 myosin was not different following unloading (0.89 ± 0.04 μm s−1) compared with control conditions (0.84 ± 0.17 μm s−1). Myosin light chain (MLC) isoform composition of type 2B myosin from hindlimb unloaded and control mice was not different. No oxidation of either type 1 or 2B myosin was observed. Higher phosphorylation of regulatory MLC in type 2B myosin after unloading was found. Conclusion Results suggest that the observed lower shortening velocity of type 2B fibres following unloading could be related to slowing of acto‐myosin kinetics in the presence of MLC phosphorylation.